Development of quantification methods for studying the emissions of isothiazolinones from building and consumer products into indoor environments. Issue 4 (September 2019) - Ducup de Saint Paul, L; Nicolas, M; Quivet, E
Abstract: Isothiazolinones, a family of biocides, are used as preservatives in a wide range of consumer and building products, such as cleaning agents, paints, or cosmetics for their fungicide, bactericide, and algaecide properties. Moreover, some isothiazolinones are classified as skin sensitizer (MIT, CMI, BIT and OIT) since they can cause eczema, oedema, or allergic contact dermatitis by dermal contact or inhalation. In this study, sensitive and robust analytical methods using GC-MS and UPLC-MS/MS as well as sampling and extraction protocols were developed to identify the emissions of seven isothiazolinones from building and consumer products. Two sampling supports (C18 Cartridge and PUF) were tested; Elution by acetonitrile for C18 Cartridge and ASE extraction using acetone and dichloromethane for PUF are chosen as extraction procedures. The first application of these developed methods on paints showed promising results.